Interpretacija i metodički pristup pjesmi The Song of Wandering Angus Williama Butlera Yeatsa - Slavić, Dean (2021)
Članak tumači životopisne okolnosti nastanka i obilježja ustroja pjesme iz naslova. Interpretacija govori o elementima ljubavne poezije potrage, konzumacije i rastanka u tumačenu tekstu, a naglašena je promjena značenja nastala mijenom naslova. Glede ustroja, istaknut je smisao opetovnosti riječi (floor, hazel, lands…) te njihova povezanost sa Staigerovim tumačenje lirike. Objašnjena je uloga broja osam, svijetlih simbola i simetričnosti u sustavu magijskoga priziva. Tekst raspravlja i o stavu ženskoga elementa u pjesmi. Metodički pristup preporučuje motivacije čitanjem učeničkih sastavaka na temu povezanu s epigrafom iz Shakespeareove drame Antonije i Kleopatra. Prikaz osjećaja kazivača i s time povezane modulacije uz svaki stih pjesme koristan je pri interpretativnom čitanju. Tumače se i rasprave, učenički eseji ili pjesme u prozi o stavu djevojke.
The article explains the biographical background and structure of Yeats" poem, The Song of Wandering Angus. Although biography is significant to the poem, and the sources are well known, the final meaning of the poem, regarding the identification of the girl in the text, remains ambiguous. In the interpretation of the poem elements of the love poetry of quest, consummation and separation, are used stressing significant shifts revealed in changes in the title. As for the structure of the poem, the significance of repetition (floor, hazel, lands, fire…) is analyzed. The role of the symbols of light, symmetry and the number eight is also examined. In the classroom students may be motivated by reading their own short essays on lines from Shakespeare"s Anthony and Cleopatra – which also constitute the epigraph of this paper. It is useful to explore the poem, line by line, by assessing the subject"s feeling and voice modulation during the stage reading. Methodology could also include debates on the trout-girl"s attitude. The exercise may be consolidated in the writing of an essay or a prose poem by having students use motifs from the poem in their texts. Students could also read extracts from Yeats" memoires and critical essays in their interpretation of the interrelation of motifs.
Bibliografske bilješke uz tekst ; bibliografija: str. 94-95.
Sažetak ; Abstract.
Keywords: The Song of Wandering Angus; Irska književnost 19./20. st. -- Irska poezija; Yeats, William Butler